Combined operation of fuse dike and service spillway - Watchara Hemruchatanun; Prida Thimakorn; Gupta, Ashim Das; Kumar, Devendra; US-ASEAN (Bangkok : Asian Institute of Technology, 1983)
An investigation was carried out to determine the optimum operation of the service spillway of Chiew Larn Dam in order to maintain both the maximum surcharge and the limiting high water level in the reservoir as controlled by the height of the fuse dike. Utilizing the head-discharge relationship from both the service spillway and the emergency spillway , reservoir routing for various inflow design floods was carried out from a number of combinations of spillway gate opening . The results obtained yield a number of combination of rises of the water level and t he outflow discharge. It was found that by means of introducing the maximum normal high water level as the starting point a nd allowing the gates to be opened gradually , the increases of the outflow discharges at the early stage of operation is gradual when compare it with the cases of fixed gate opening or step opening.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Spillways; Chiew Larn Dam